Impact of air pollution on health in Klang Valley, Malaysia - Rafia, Afroz; Hassan, Mohd Nasir; Awang, Muhamad; Ibrahim, Akma (IOI press, 2006)
In Malaysia, as in other parts of the world, air pollution has recently been receiving priority among environmental issues. The ambient atmospheric conditions have been progressively deteriorating due to unprecedented growth in urbanization, number of motor vehicles and continuous industrial development. Monitoring data and studies on ambient air quality show that the ambient air quality of the country is clean in general but some of the air pollutants in several large cities especially in Klang Valley, the most densely populated area, are increasing with time and are not always at acceptable levels according to the national ambient air quality standards. This research employed contingent valuation method (CVM) to estimate the willingness to pay of the respondents to avoid the illness episodes due to air pollution. To evaluate the impact of additional information on the willingness to pay (WTP) of the respondents, different sub-samples were presented with contingent valuation scenarios offering different levels of information. One sub-sample was given the cause of ill-health episodes and the policy to be implemented to remedy the cause of the ill-health episodes (context version). Another sub-sample was asked to value the avoidance of episodes of ill-health, but was not given any details of the cause of the episodes nor the policy that would be implemented to remedy the cause of ill-health episodes (non-context version). The study has found that the inclusion of additional information in the presentation of scenarios in contingent valuation exercises significantly influenced WTP for the avoidance of ill-health episodes. The average mean value of WTP of the respondents for the context version was higher than that of the non-context version i.e. RM154 for the context version and RM134 for the non-context version. Since, WTP to avoid the ill-health episodes cannot be shown to be independent of the context in which it is valued, the validity of transferring benefits of avoided ill-health episodes from one country to another must be called into question and the results of the study will not allow decision makers to apply the estimated values for the avoidance of ill-health episodes in the consideration of policies with very different context.